2014
DOI: 10.1371/journal.pone.0085039
|View full text |Cite
|
Sign up to set email alerts
|

A New Class of Pluripotent Stem Cell Cytotoxic Small Molecules

Abstract: A major concern in Pluripotent Stem Cell (PSC)-derived cell replacement therapy is the risk of teratoma formation from contaminating undifferentiated cells. Removal of undifferentiated cells from differentiated cultures is an essential step before PSC-based cell therapies can be safely deployed in a clinical setting. We report a group of novel small molecules that are cytotoxic to PSCs. Our data indicates that these molecules are specific and potent in their activity allowing rapid eradication of undifferentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…New synthesized small molecules (such as JC011), which selectively induce a cytotoxic endoplasmic reticulum stress response in ESCs and iPSCs, have also been reported, but further studies should reveal the precise mechanisms of this pathway. 12 We believe that two issues relating to the use of ESC or iPSC therapies need to be addressed. After treating cells with chemical inhibitors to prevent teratoma, these cells should be tested to ensure that they have maintained functional properties, including differentiation capacity 13 and engraft ment potential.…”
mentioning
confidence: 99%
“…New synthesized small molecules (such as JC011), which selectively induce a cytotoxic endoplasmic reticulum stress response in ESCs and iPSCs, have also been reported, but further studies should reveal the precise mechanisms of this pathway. 12 We believe that two issues relating to the use of ESC or iPSC therapies need to be addressed. After treating cells with chemical inhibitors to prevent teratoma, these cells should be tested to ensure that they have maintained functional properties, including differentiation capacity 13 and engraft ment potential.…”
mentioning
confidence: 99%
“…A) Small molecules that have been reported to prevent teratoma formation in stem cell cultures. [11][12][13] B) Structures of IV-1 and IV-7,which are potentc ytotoxica nalogues of YM155. [17] Figure 2.…”
Section: Resultsmentioning
confidence: 99%
“…[10] Thed eploymento fs mall molecules to selectively removeu ndifferentiated pluripotent cells has received attention as av iable alternative. [11][12][13] This pharmacological approach has several advantages:i ti sr obust, rapid, andc ost-effective, maintains genetics tability of cells, minimizesc ell attrition,a nd has good translational potential, as it can be appliedt oc omplex differentiation protocols. Figure 1A shows small molecules that have been reportedt oi nhibit the formation of stem-cellderived teratomas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A high-throughput inhibitor screen revealed that the SCD1 inhibitor, also called pluripotent cell-specific inhibitor #1 (PluriSIn #1) induces endoplasmic reticulum (ER) stress, inhibits protein synthesis and leads to apoptosis in hESC and hiPSC (Ben-David et al 2013). Similar approaches led to the finding of further inhibitors (JC011, JC010, JC017, JC040) targeting the ER of undifferentiated hESC (Richards et al 2014). Treatment with the DNA topoisomerase inhibitor etoposide results in depletion of undifferentiated hiPSC from cardiac progenitor populations.…”
Section: Tumorigenicity Of Hesc and Hipscmentioning
confidence: 99%